2010
DOI: 10.1111/j.1365-3032.2010.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of visual and olfactory cues for host location in the mustard leaf beetle Phaedon cochleariae

Abstract: The relevance of visual and olfactory cues for host‐plant location is investigated in males and females of the oligophagous mustard leaf beetle Phaedon cochleariae Fabricius (Coleoptera: Chrysomelidae). Different objects are offered in a walking arena and the behaviour of beetles is observed. Beetles orient toward vertically or horizontally striped black and white pattern independent of stripe orientation. The results suggest that contrast facilitates orientation in the field, whereas the pattern itself may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
4
15
1
1
Order By: Relevance
“…Also, the current trap data do not support the hypothesis that there are differences between male and female pollen beetles regarding their behavioural responses to spectral stimuli. This is in contrast to other studies that find sexual dimorphism with regard to colour choice behaviour in other beetle species (Crook et al , 2009; Kühnle & Müller, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Also, the current trap data do not support the hypothesis that there are differences between male and female pollen beetles regarding their behavioural responses to spectral stimuli. This is in contrast to other studies that find sexual dimorphism with regard to colour choice behaviour in other beetle species (Crook et al , 2009; Kühnle & Müller, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…The superior role of visual cues is in line with other studies which revealed that visual cues of plant parts perceived by adult herbivores can be more relevant and override olfactory cues in host finding and location (Stenberg & Ericson, 2007;Kühnle & Müller, 2011). The possibility cannot be excluded that the excised condition in which flowers and leaves were offered affected the choice.…”
Section: Cues Driving Preferences For Flowers Versus Leavessupporting
confidence: 80%
“…In HD okra monocultures, the additional green surfaces were okra plants and thus leaf beetle numbers decreased only slightly in these plots in comparison with other HD plots. The importance of visual contrasts on beetles has been shown by previous studies . By contrast to leaf beetles and whiteflies, aphid abundance increased in HD plots.…”
Section: Discussionsupporting
confidence: 64%
“…Polyphagous aphids and whiteflies often respond to the spectra of greenish‐yellow light reflected by vegetation, or to the contrast in the plant–soil landscape, as they have not developed host‐specific olfactory cues. The relevance of visual cues in host‐searching abilities has also been shown for oligophagous leaf beetles . Therefore, it is evident that in intercropping systems the identity of the additional crop species, and of the pest, can be crucial in determining the pest suppression success of the intercropped field design.…”
Section: Introductionmentioning
confidence: 98%